Genetic parameters and performance of sugarcane families under cold stress in the South of Brazil - Verissimo, Mario Alvaro Aloisio; Oliveira, Ricardo Augusto de; Silva, Sérgio Delmar dos Anjos e; Daros, Edelclaiton; Härter, Adilson (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to estimate the genetic parameters for the performance prediction of sugarcane (Saccharum spp.) families under natural cold stress, in Southern Brazil, and to identify the best combinations of parents aiming at the selection for tolerance to cold. Fifty-three full-sib families were evaluated in an incomplete block design, with five replicates per family, in the municipality of Pelotas, in the state of Rio Grande do Sul, Brazil. Harvest occurred in August 2013, nine months after planting and after cold spells with negative temperatures down to -2.2ºC. Statistical analyses, performed with the mixed model methodology, detected significant differences among families. Heritability estimates among progeny means were higher than those of individual heritability. Estimates of genetic progress for the traits megagrams of stalks per hectare, megagrams of brix per hectare, and number of stalks indicated gains of 93.8, 91.0, and 53.3%, respectively. A set of eight promising families that combine high estimates for yield and cold stress tolerance was obtained.